The Correlation between Personality and Family Support and Subjective Well-Being for Patients with Diabetes Mellitus - Pratiwi, Ika Nur; Kusnanto; Maulida, Yolanda Eka (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes mellitus is a chronic disease characterized by elevated blood sugar levels because the pancreas does not produce enough insulin. People with diabetes mellitus who looked at the negative condition need to be reviewed from a psychological perspective. Factors that may affect subjective well-being (SWB) are the support of family and personality. The purpose of this study was to analyze the relationship between family support and patients’ personality with subjective well-being in patients with Diabetes mellitus. This research used a cross- sectional design. Respondents were selected from five primary health centers with the highest number of DM cases in Surabaya, Indonesia with a total of 102 respondents. Data were collected using a personality questionnaire, family support questionnaire and SWB questionnaire. Furthermore, the data were analyzed using Rank Spearman test with a significance level < 0,05. The result showed that 81 respondents were female, aged 46-55 years and married. There was a significant correlation between personality and SWB (p= 0,008; r = 0,260). In addition, the family support also significantly correlated with SWB (p = 0,011; r = 0,249). The higher the value of positive personality and family support they had, the higher the value of subjective well-being.